ApoE4 upregulates the activity of mitochondria‐associated ER membranes. (12th November 2015) - Tambini, Marc D; Pera, Marta; Kanter, Ellen; Yang, Hua; Guardia‐Laguarta, Cristina; Holtzman, David; Sulzer, David; Area‐Gomez, Estela; Schon, Eric A
Abstract: In addition to the appearance of senile plaques and neurofibrillary tangles, Alzheimer's disease (AD) is characterized by aberrant lipid metabolism and early mitochondrial dysfunction. We recently showed that there was increased functionality of mitochondria‐associated endoplasmic reticulum (ER) membranes (MAM), a subdomain of the ER involved in lipid and cholesterol homeostasis, in presenilin‐deficient cells and in fibroblasts from familial and sporadic AD patients. Individuals carrying the ε4 allele of apolipoprotein E (ApoE4) are at increased risk for developing AD compared to those carrying ApoE3. While the reason for this increased risk is unknown, we hypothesized that it might be associated with elevated MAM function. Using an astrocyte‐conditioned media (ACM) model, we now show that ER–mitochondrial communication and MAM function—as measured by the synthesis of phospholipids and of cholesteryl esters, respectively—are increased significantly in cells treated with ApoE4‐containing ACM as compared to those treated with ApoE3‐containing ACM. Notably, this effect was seen with lipoprotein‐enriched preparations, but not with lipid‐free ApoE protein. These data are consistent with a role of upregulated MAM function in the pathogenesis of AD and may help explain, in part, the contribution of ApoE4 as a risk factor in the disease. Synopsis: The reason why ApoE4 is a risk factor in Alzheimer's disease is unknown. This study shows that lipoproteins containing ApoE4, but not those containing ApoE3, upregulate the communication between ER and mitochondria at mitochondria‐associated ER membranes (MAM), and may help explain, in part, the role of ApoE4 as a risk factor in the disease. ER–mitochondrial communication and MAM function are increased in cells treated with ApoE4‐containing ACM ApoE4 exerts its effects on MAM when incorporated into lipoprotein particles, not as the free protein These findings suggest that ApoE4's role in AD is associated with perturbed cholesterol homeostasis. Abstract : The reason why ApoE4 is a risk factor in Alzheimer's disease is unknown. This study shows that lipoproteins containing ApoE4, but not those containing ApoE3, upregulate the communication between ER and mitochondria at mitochondria‐associated ER membranes (MAM), and may help explain, in part, the role of ApoE4 as a risk factor in the disease.